The Role of microRNAs in Alcoholism: A Meta-analytic Review - Mohebbati, Reza; Sadeghnia, Hamid R. (Current Pharmaceutical Design, 2022)
Introduction: A growing body of evidence indicates that repeated alcohol exposure or withdrawal from alcohol can result in persistent molecular and cellular adaptations. One molecular adaptation that occurs is the regulation of gene expression, which is believed to lead to functional alterations that characterize addiction. MicroRNAs (miRs) have been recently identified as master regulators of gene expression through posttranscriptional regulation. The aim of this meta-analytic review was to evaluate the regulatory forms of miRs during alcoholism. Methods: We used several databases such as PubMed, Scopus, and Web of Science without limitations on publication time. All studies were analyzed by Comprehensive Meta-Analysis software. Results and Discussion: Six clinical papers with 243 alcoholic patients and 162 controls were included. In this study, 1680 articles were initially reviewed and eventually, six clinical studies were included in the metaanalysis. The results of the meta-analysis showed that according to the random model, the difference between the upregulation and downregulation of central addiction targets was statistically significant, indicating that most dopamine- or gamma-aminobutyric acid receptor subunit (GABA)-related miRs are upregulated in alcoholics (P: 0.00, CI: 0.149-0.439). Conclusion: This study strongly suggests that dopamine- or GABA-related miRs were mostly upregulated in alcoholism. Our findings revealed that about 9% of miRs were downregulated in alcoholism, including miR- 567, miR-126, miR-1, miR-432, and miR-153. To identify other or specific miRs as potential biomarkers in alcoholics, large-scale studies and more clinical work are required.
Keywords: biomarker